Legal Policy of Responsibility For Unlawful Acts of Directors in Managing State-Owned Enterprises - Nurahmawati, Pani; Gultom, Elisatris; Perwira, Indra (Journal of Ecohumanism, 2024)
State-owned enterprises (SOEs) play an important role in the Indonesian economy, not only as economic entities but also as agents of social development. SOE directors are responsible for managing the company, including strategic decision-making, human resource management, and risk management. However, they often face various challenges, including political intervention, bureaucracy, and transparency issues. The phenomenon of unlawful acts in the management of SOEs, such as corruption and abuse of authority, is a serious problem that can damage integrity and public trust. This study uses a normative and descriptive analytical approach to examine the legal responsibility of SOE directors in the context of unlawful acts. The study results indicate that firm and transparent legal responsibility is essential to ensure the accountability and sustainability of SOEs. Improvement steps are needed in the supervision and law enforcement system to prevent unlawful acts and improve the integrity and credibility of SOEs as the driving force of the country’s economy.